Analysis of the Capital Asset Pricing Model (CAPM) Method to Determine Investment Options in LQ45 Stocks on the Indonesia Stock Exchange (IDX) for the 2019-2023 Period - Setyawan, Dwi Aris; Mutamimah, Mutamimah (Journal of Advanced Multidisciplinary Research, 2025)
Stock valuation is a crucial component of investment analysis, helping investors make informed decisions amid fluctuating market conditions. Despite its popularity, the Capital Asset Pricing Model (CAPM) often yields inconsistent results in practice, especially in emerging markets such as Indonesia. Previous studies have not sufficiently addressed how effectively CAPM distinguishes undervalued and overvalued stocks in the LQ45 Index, which comprises high-capitalization and liquid stocks on the Indonesia Stock Exchange (IDX). This study aims to assess the performance of CAPM in identifying mispriced stocks and guiding portfolio decisions. A total of 23 stocks were selected from the LQ45 Index based on their consistent inclusion from 2019 to 2023 and complete data availability. The analysis utilizes daily closing stock prices, the Jakarta Composite Index (JCI) as a market proxy, and the Bank Indonesia 7-Day Reverse Repo Rate as the risk-free rate. The results reveal six undervalued stocks: PT Aneka Tambang Tbk (ANTM), PT Bank Rakyat Indonesia (Persero) Tbk (BBRI), PT Bank Mandiri (Persero) Tbk (BMRI), PT XL Axiata Tbk (EXCL), PT Hanjaya Mandala Sampoerna Tbk (HMSP), and PT Media Nusantara Citra Tbk (MNCN). Meanwhile, 17 stocks are categorized as overvalued, including PT Adaro Energy Indonesia Tbk (ADRO), PT Astra International Tbk (ASII), PT Bank Central Asia Tbk (BBCA), PT Indofood CBP Sukses Makmur Tbk (ICBP), and others. These findings confirm that CAPM remains a useful tool in valuing stocks and shaping rational investment strategies. The study contributes to a better understanding of CAPM’s empirical relevance in emerging capital markets and provides practical insights for investors and financial analysts.